Inclusive Communication in Dakwahtainment: Da'wah Strategies for Minority Groups through the ‘Log In’ Podcast - Suci Ramadhani; Hasan Sazali; Retno Sayekti (PT Agung Media Publisher, 2025)
The emergence of digital media has transformed Islamic preaching into more interactive and inclusive forms. One such innovation is the Log In Podcast, which combines religious messages with entertainment (dakwahtainment) and features interfaith dialogue. This study explores how inclusive communication strategies are applied in the Log In Podcast Season 3, particularly in engaging religious and cultural minorities. This qualitative research uses a descriptive approach with content analysis techniques. Data were gathered from eight episodes of the Log In YouTube podcast and audience comments. NVivo 12 software was used for coding and thematic mapping of both the content and responses. The analysis reveals three key indicators of inclusive da’wah namely diverse guest speakers (including Muslims, Christians, Buddhists, and cultural figures), a wide range of themes (such as tolerance, psychology, sharia, and the arts), and positive audience engagement. Comments reflect appreciation for the open, respectful tone and the podcast’s ability to bridge religious differences. Figures like Habib Ja’far play a central role in mediating dialogue, while audiences respond enthusiastically to recurring interfaith guests and inclusive discussions. The Log In Podcast succeeds as a platform for inclusive digital da’wah, creating a space where religious diversity is respected and discussed. This approach not only appeals to Muslim audiences but also engages minorities and non-Muslims, fostering interfaith understanding. The podcast demonstrates how social media can be effectively used for pluralistic and modern religious communication.